2014
DOI: 10.1073/pnas.1321942111
|View full text |Cite
|
Sign up to set email alerts
|

PAI-1–regulated extracellular proteolysis governs senescence and survival in Klotho mice

Abstract: Cellular senescence restricts the proliferative capacity of cells and is accompanied by the production of several proteins, collectively termed the "senescence-messaging secretome" (SMS). As senescent cells accumulate in tissue, local effects of the SMS have been hypothesized to disrupt tissue regenerative capacity. Klotho functions as an aging-suppressor gene, and Klotho-deficient (kl/kl) mice exhibit an accelerated aging-like phenotype that includes a truncated lifespan, arteriosclerosis, and emphysema. Beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(141 citation statements)
references
References 45 publications
8
124
0
Order By: Relevance
“…[25][26][27][28] First, in spns1 hi891/ hi891 fish embryos, our qRT-PCR experiments showed that the expression of glb1 was more than 2-fold enhanced, and serpine1/pai-1 expression, which can also be elevated in cellular and organismal senescence, [29][30][31] became more than 3-fold through 8-fold higher, with the advancing opaque yolk phenotype ( Fig. 6A and B).…”
Section: Concurrent Heritable Defects Of Both Spns1 and Atp6v0ca In Zmentioning
confidence: 86%
“…[25][26][27][28] First, in spns1 hi891/ hi891 fish embryos, our qRT-PCR experiments showed that the expression of glb1 was more than 2-fold enhanced, and serpine1/pai-1 expression, which can also be elevated in cellular and organismal senescence, [29][30][31] became more than 3-fold through 8-fold higher, with the advancing opaque yolk phenotype ( Fig. 6A and B).…”
Section: Concurrent Heritable Defects Of Both Spns1 and Atp6v0ca In Zmentioning
confidence: 86%
“…In conclusion, we herein propose a previously unrecognized function for extracellular Pi in the regulation of the aging process. Because the blockade of calpain 1 or a plasminogen activator inhibitor-1 deficiency in Kl 2/2 mice is known to extend longevity, 39,40 further analyses are warranted to determine the importance of the proposed pathway in this context. Our results are clinically important because they provide a were plotted.…”
Section: Discussionmentioning
confidence: 99%
“…For other indications, there are no models or only ones that are imperfect. Certain genetically modified mice have been developed that resemble human progerias and other syndromes that are caused by single-gene mutations (Baker et al 2008;Chen et al 2013;Tchkonia et al 2013;Eren et al 2014). In such mice, it is possible to evaluate drug candidates for effectiveness in alleviating aging-like or health-span phenotypes, such as insulin resistance, weakness, decreased endurance, reduced activity, or neurological dysfunction.…”
Section: Preclinical Studiesmentioning
confidence: 99%